Tuning the NIR photoabsorption of CuWO4−x nanodots with oxygen vacancies for CT imaging guided photothermal therapy of tumors. (29th August 2019) - Wen, Mei; Wang, Shun; Jiang, Ruiqi; Wang, Yue; Wang, Zhaojie; Yu, Wanjian; Geng, Peng; Xia, Jindong; Li, Maoquan; Chen, Zhigang
Abstract : NIR photoabsorption of CuWO4− x can be tuned, and the resulting CuWO4− x nanodots can act as efficient all-in-one nanoagent for simultaneous CT/IR imaging and photothermal therapy of tumors. Abstract : A traditional CuWO4 semiconductor ( E g = 2.25 eV) shows photoabsorption in the visible range with an edge at ∼550 nm, limiting its application in near-infrared (NIR) laser-induced photothermal ablation therapy (PAT). To tune the NIR photoabsorption of CuWO4, we report a trisodium citrate-induced strategy for generating oxygen vacancies. CuWO4 and CuWO4− x nanoparticles are prepared by a facile coprecipitation–solvothermal method in the absence or presence of trisodium citrate (0.2–0.5 g) as the reducing agent. Without trisodium citrate, CuWO4 consists of aggregated particles, and its dispersion has a typical yellow-green color without NIR photoabsorption. With the addition of trisodium citrate from 0.2 to 0.5 g, CuWO4− x samples are composed of monodisperse nanodots with increased sizes from ∼2 to ∼6 nm, and the color of these dispersions becomes darker with increased NIR photoabsorption, that is, from 0.178 to 0.685 at 808 nm. As a result, the aqueous dispersion of CuWO4− x -0.5 nanodots prepared with 0.5 g trisodium citrate exhibits a high photothermal efficiency of 47.6% under 808 nm laser irradiation. Simultaneously, CuWO4− x -0.5 nanodots have high X-ray attenuation as a CT imaging agent due to the presence of a heavy metal element (W). When the CuWO4− x -0.5 dispersion is injected into the tumors of mice, the tumors can be observed by CT and thermal imaging. After 808 nm laser irradiation (1.0 W cm −2, 10 min), cancer cells in vivo can be efficiently ablated by the photothermal effects of CuWO4− x, without obvious toxicity and side effects. Therefore, CuWO4− x can act as a novel all-in-one agent for CT imaging-guided photothermal therapy of tumors.